COMUNICAÇÃO COMUNITÁRIA E MÍDIA-EDUCAÇÃO: ÁREAS DISTINTAS E CONVERGENTES - Nishiyama, Alexandra Fante (2011)
The objective of this study was to determine whether the epistemological field of Community Communication and Media-education even distinct, are convergent. The research method was qualitative and the technical literature. A first survey was done in all publications of PhD theses and dissertations published on the site Capes Coordination for the Improvement of Higher Education, Ministry of Education, between the years 2000 to 2009 For the survey, noted are fostering the polls in 2008 and 2009, focusing the analysis in these years. To filter content were used the keywords: Community Communication; Media education, Educomunication Communication and Education. It was found that the Community Communication and Media-education work in order to achieve the same goals, even for roads, ways, becoming convergent areas.